Victims of war : an empirical study on war-victimization and victims attitudes towards addressing atrocities - Kiza, Ernesto (Hamburger Edition HIS Verlagsges. mbH, 2006)
The major goal of the unique and groundbreaking »Victims of War« project was to deliver explorative empirical data on the topic of macro-victimization in wars. After identifying a major research gap in the important areas of conflict resolution, transitional justice research, and especially victimology / criminology, a group of researchers at the Max Planck Institute for Foreign and International Criminal Law (Freiburg, Germany) decided to approach the exploration of the field based on a victimological understanding. The victimological perspective of the project is innovative since it addresses phenomena that are outside the classical scope of victimology—which studies regular crime and deviance instead of international crimes— and provides a path for the overdue broadening of the discipline as well as first-time empirical evidence on victims’ needs in war and post-war situations. With the help of a bottom-up approach, systematic, interdisciplinary, and international-comparative knowledge about the structure of victimization and the desires of victims regarding their needs to overcome victimization in a context of contemporary wars was generated. In order to approach the research problem, 991 war victims in 11 different countries and regions were surveyed. This yielded information on respondents’ victimization experiences and their opinions towards major aspects of transitional justice research, which addresses various questions of formal and informal conflict resolution mechanisms in countries transitioning from one system to another, including war-torn societies. This wide perspective also encompasses the evolving area of International Criminal Justice (ICrimJ).